Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.20944/preprints202107.0584.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Future Precipitation Patterns in the Lake Victoria Basin Using CMIP6 Projections

Abstract: In late/early 2019/2020, unprecedented high-water-levels were observed in Lake Victoria causing massive flooding in the low-lying lake-adjacent areas and disrupting human and natural systems in the Lake Victoria Basin (LVB). The high lake water-level coincided with unusually heavy and prolonged 2019 June to December precipitation in the LVB. The current study estimates future precipitation patterns over the LVB using HighResMIP and ScenarioMIP general circulation model (GCM) simulations from the 6th phase of t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Annually, dry spells are projected to increase under SSP1-2.6, decrease under SSP2-4.5 and SSP5-8.5 over most parts of the IGAD region. It appears that a rise in the number of rainy days and a decrease in dry spells explains the enhanced rainfall signals found by Mbigi et al 71 over Uganda and Kenya, Ogega et al 72 over Lake Victoria basin as well as the growing trend reported by Alaminie et al 73 over Ethiopia's Upper Blue Nile Basin and Ngoma et al over Uganda 74 .
Figure 13 Spatial pattern of projected number of dry spells over the IGAD region based on CMIP6 ensemble mean for the near future (2021–2050) and far future (2071–2100) relative to the baseline period (1985–2014).
…”
Section: Resultsmentioning
confidence: 87%
“…Annually, dry spells are projected to increase under SSP1-2.6, decrease under SSP2-4.5 and SSP5-8.5 over most parts of the IGAD region. It appears that a rise in the number of rainy days and a decrease in dry spells explains the enhanced rainfall signals found by Mbigi et al 71 over Uganda and Kenya, Ogega et al 72 over Lake Victoria basin as well as the growing trend reported by Alaminie et al 73 over Ethiopia's Upper Blue Nile Basin and Ngoma et al over Uganda 74 .
Figure 13 Spatial pattern of projected number of dry spells over the IGAD region based on CMIP6 ensemble mean for the near future (2021–2050) and far future (2071–2100) relative to the baseline period (1985–2014).
…”
Section: Resultsmentioning
confidence: 87%